(untitled) (Marketing Journal, 2025)
The article examines the issues of implementing a strategic approach and effective management systems in enterprises to maintain competitiveness and a stable position in the market in modern economic conditions, and the author argues that this process is of particular importance in the garment and knitwear industry, which is one of the sectors with high export potential. The authorʼs approach is also based on the fact that the long -term success of enterprises in a time of increasing competition depends on how correctly and timely strategic decisions are made.